The Use Of Code-Switching By Teacher In Classroom Interaction At MAN 2 Model Medan - Muhammad Zakky Mubarak; Utami Dewi; Deasy Yunita Siregar (VISION, 2022)
This research that has been conducted entitled "The Use of Code-Switching By Teacher In Classroom Interaction At MAN 2 Model Medan" which is motivated by the fact that there are differences in abilities between teachers and students in using and understanding English so make the teacher adjust the language gap so that code-switching occurs between students and teachers in classroom interaction. Code-switching is a communication between people use two or more language. The research methodology in this study use a qualitative method where the data collected by the researcher was by triangulation method that are observation, documentation and interview the teacher. The results obtained by the researcher are three types of code-switching used by teachers in classroom interaction, those are tag switching, inter-sentential switching, and intra-sentential switching. Based on those three types, the dominant types that are most often used by the teacher is inter-sentential switching. The teacher use code switching because of talking about particular topic, quoting somebody else, showing empathy, interjection, repetition, expressing group identity, and to clarify about the content. Based on the finding of the research, it can be concluded that code-switching can be used by teacher in classroom interaction because code-switching as the solution of the language gap between teacher and student.